Knowledge, attitude, and practice on non-communicable diseases (NCDs) among the adult population in the urban area of Negeri Sembilan, Malaysia - Ithnin M.; Effendy N.M.; Sahar M.A.; Abdullah K.H.A.; Muhammad Shamsir Mohd Aris; Rani M.D.M.; Nadeeya'ayn Umaisara Mohamad Nor; Norsham Juliana Nordin (J. K. Welfare and Pharmascope Foundation, 2024)
Indexed by Scopus